Emotion Regulation and Stress Reactivity in the Adolescent Daughters of Depressed Mothers - Foot, Meredith L (Université d'Ottawa / University of Ottawa, 2011)
The daughters of women with a history of depression are at heightened risk for a range of mental health problems. The present study investigated emotion regulation, cortisol reactivity to stress, and interpersonal competence as potential indicators of risk in adolescent girls at high versus low risk for depression. Participants were a community sample of 47 girls and their mothers (27 high risk and 20 low risk). Mothers and daughters had been interviewed to assess diagnostic history as part of a previous longitudinal study. In the current study, daughters completed the Trier Social Stress Test for Children (TSST-C) and cortisol samples were collected before and after exposure to this psychosocial stressor. Both mothers and daughters completed self-report questionnaires and daughters were re-assessed using the Depressive Disorders module of the Kiddie Schedule for Affective Disorders and Schizophrenia. High risk mothers were also interviewed to assess the timing and chronicity of their depressive episodes during their daughters’ lifetime. High and low risk girls had equivalent ratings of self-reported stress following the TSST-C, but different physiological responses. Girls at high risk for depression showed a blunted cortisol response to the TSST-C whereas low risk girls showed a normal cortisol response. High risk status for depression predicted a blunted cortisol response to stress, which predicted difficulties with emotion regulation; difficulties with emotion regulation in turn predicted a greater number of self-reported depressive symptoms. These results suggest that maternal depression may act as a stressor that compromises stress-response system functioning in daughters and produces related difficulties with emotion regulation.
Keywords: maternal depression; depression; adolescents; cortisol; emotion regulation; interpersonal competence; stress reactivity